Pro-apoptotic Sorafenib signaling in murine hepatocytes depends on malignancy and is associated with PUMA expression in vitro and in vivo - Sonntag, R (Nature Publishing Group, 2014)
The multi-kinase inhibitor Sorafenib increases the survival of patients with advanced hepatocellular carcinoma (HCC). Current data suggest that Sorafenib inhibits cellular proliferation and angiogenesis and promotes apoptosis. However, the underlying pro-apoptotic molecular mechanisms are incompletely understood. Here we compared the pro-apoptotic and anti-proliferative properties of Sorafenib in murine hepatoma cells and syngeneic healthy hepatocytes in vitro and in animal models of HCC and liver regeneration in vivo. In vitro, we demonstrate that cell cycle activity and expression of anti-apoptotic Bcl-2 like proteins are similarly downregulated by Sorafenib in Hepa1-6 hepatoma cells and in syngeneic primary hepatocytes. However, Sorafenib-mediated activation of caspase-3 and induction of apoptosis were exclusively found in hepatoma cells, but not in matching primary hepatocytes. We validated these findings in vivo by applying an isograft HCC transplantation model and partial hepatectomy (PH) in C57BL/6 mice. Sorafenib treatment activated caspase-3 and thus apoptosis selectively in small tumor foci that originated from implanted Hepa1-6 cells but not in surrounding healthy hepatocytes. Similarly, Sorafenib did not induce apoptosis after PH. However, Sorafenib treatment transiently inhibited cell cycle progression and resulted in mitotic catastrophe and enhanced non-apoptotic liver injury during regeneration. Importantly, Sorafenib-mediated apoptosis in hepatoma cells was associated with the expression of p53-upregulated-modulator-of-apoptosis (PUMA). In contrast, regenerating livers after PH revealed downregulation of PUMA and were completely protected from Sorafenib-mediated apoptosis. We conclude that Sorafenib induces apoptosis selectively in hepatoma cells but not in healthy hepatocytes and can additionally increase non-apoptotic hepatocyte injury in the regenerating liver.